Praktik mentoring perkawinan poligami oleh coach Hafidin: Perspektif hukum positif dan hak asasi manusia - aini, Intan Nur’ (Maliki Interdisciplinary Journal, 2024)
Polygamous marriage is still a phenomenal issue among Indonesian people. Lately, people who practice polygamy do not hesitate to show it off on social media. There is even a religious figure who opens a polygamy mentoring class. This is like what coach Hafidin did. Coach Hafidin opened a polygamy mentoring class using a paid seminar. Through several existing youtube channels, there are several statements that contain controversy among the public. This study aims to describe the practice of polygamy carried out by coach Hafidin, describing polygamy mentoring from a positive legal perspective and Human Rights. This study uses a juridical-normative type with a focus on the mentoring of polygamous coach Hafidin. The results of this study show that coach Hafidin’s polygamous mentoring is not in accordance with existing regulations, positive law and also violates the rights of a woman.